Prasasti Sapu Angin: Analisis Isi, Makna, dan Legitimasi - Megarismi, Ratri Juang (Jambura History and Culture Journal, 2025)
The Sapu Angin Inscription is a sima inscription issued by Krtajaya before he ascended the throne. This study discusses the content and meaning of the Sapu Angin Inscription, supported by evidence indicating that Krtajaya is the same person as the subsequent king, Śrī Mahārāja Śrī Śarwweśwara Triwikramāwatārānindita Śṛnggalañchana Digjayotunggadewanāma. The study also explores the historical background of the inscription’s issuance, which is closely related to Krtajaya’s process of gaining legitimacy. This research employs a qualitative-descriptive method with a historical approach. The findings reveal that the Sapu Angin Inscription indeed belongs to Krtajaya, who is also known by the full royal title Śrī Mahārāja Śrī Śarwweśwara Triwikramāwatārānindita Śṛnggalañchana Digjayotunggadewanāma. Furthermore, the Sapu Angin Inscription functioned as a political strategy and a form of gradual legitimization for Krtajaya prior to his official coronation.